The efficacy of intrauterine infusion of platelet rich plasma in women undergoing assisted reproduction: a systematic review and meta-analysis - Noran Magdy Shalma; Hazem Mohamed Salamah; Ashraf Alsawareah; Ahmad Shehata Shaarawy; Mohamed Reyad Mohamed; Emery Manirambona; Mohamed Abd-ElGawad (BMC, 2023)
Abstract Background Platelet-rich plasma (PRP) is an autologous platelet concentration recently used in the reproductive field. Studies had conflicting results regarding its effect on pregnancy outcomes. We aimed to solve the debate on the safety and efficacy of PRP in women undergoing assisted reproduction and assess the influence of covariates on the outcomes of PRP infusion. Methods We searched PubMed, Scopus, Cochrane, and Web of Science in May 2023. We included randomized and non-randomized clinical trials as well as cohort studies assessing intrauterine PRP in sub fertile women undergoing assisted reproduction (IVF/ICSI). For the quality assessment, We used the Cochrane Risk of Bias Tool 1, the ROBINS-I tool, and the Newcastle-Ottawa Scale. We pooled the data using RevMan version 5.4. Results The data from 23 studies were pooled. PRP had favorable outcomes compared with the control group on clinical pregnancy rate (RR: 1.84, 95% CI 1.62 to 2.09; P < 0.00001), live birth rate (RR: 1.75, 95% CI: 1.24 to 2.47; P = 0.001), and miscarriages (RR: 0.51, 95% CI: 0.36 to 0.72; P = 0.0002). Women with repeated implantation failure had a significantly improved clinical pregnancy rate (RR: 1.83, 95% CI: 1.49 to 2.24; P < 0.00001), live birth rate (RR:1.83, 95% CI: 1.33 to 2.51; P = 0.002), and miscarriage rate (RR: 0.46, 95% CI: 0.31 to 068; P = 0.0001). Conclusion PRP showed promising results in assisted reproductive techniques. Further large and multicenter RCTs are required to compare the doses of PRP while identifying the specific population with the most benefits from PRP.